Drainage system evaluation and control of inundation in campus and housing areas of ITS, Surabaya - Eldo Fikri Alvin; Mas Agus Mardyanto (Sustinere: Journal of Environment and Sustainability, 2017)
The campus area of the Sepuluh Nopember Institute of Technology (Institut Teknologi Sepuluh Nopember/ITS) and its housing complex are often inundated during heavy rain. This is primarily due to the relatively flat topography of the campus area. Moreover, sediment accumulation in some existing drainage channels reduces their optimum capacity. Therefore, an evaluation of ITS’s drainage system needs to be conducted.This evaluation was carried out in stages with the following steps: identification of existing problems, collection of primary and secondary data, literature review, calculation of the capacity of existing channels, runoff estimation, and analysis of existing retention ponds. The primary data included flow direction, channel slope and dimensions, and sediment thickness in the channels. The secondary data comprised rainfall intensity, the ITS master plan, and land use data. The calculations included engineering design, the bill of quantity (BOQ), and budget estimation. Additionally, a standard operating procedure for drainage system maintenance was suggested to optimize channel performance.From the analysis, it was found that the maximum daily rainfall is 136.09 mm/day for a 5-year return period and 159.19 mm/day for a 10-year return period. Inundation around ITS occurs due to several factors. Some drainage channels are not connected to each other, preventing smooth water flow to the receiving water body (river). Additionally, certain channels were not constructed with the proper slope, further contributing to drainage issues. Road inundation is also caused by the absence of street inlets, preventing water from flowing into the side channels.It can be concluded that in some areas, the number of secondary drainage channels and box culverts needs to be increased, the slope of certain channels should be adjusted, and a total of 288 street inlets must be constructed throughout the planning area.